Differentiation-Dependent Regulation of Human Endogenous Retrovirus K Sequences and Neighboring Genes in Germ Cell Tumor Cells - Mueller, Thomas; Hantsch, Claudia; Volkmer, Ines; Staege, Martin S. (Frontiers in Microbiology, 2018)
Under physiological conditions, most human endogenous retroviruses (HERVs) are transcriptionally silent. However, re-activation of HERVs is observed under pathological conditions like inflammation or cancer. In addition to expression of HERV sequences, an impact of HERV-loci on expression of adjacent genes has been suggested as probably important patho-physiological mechanism. A candidate for such a gene is PRODH (proline dehydrogenase 1), which is located on chromosome 22 adjacent to HERVK-24. Germ cell tumors (GCT) are known to express high level of HERVK sequences. In addition, non-seminomatous GCT are useful models to study HERV expression in the context of differentiation since they reflect aspects of cellular development during embryogenesis and usually contain different cell types. This is due to the embryonal carcinoma (EC) cells, which are the stem cell component of GCT. They are pluripotent, show high expression of pluripotency markers like OCT4 and LIN28A and can differentiate into either somatic derivatives (teratoma cells) or choriocarcinoma or yolk-sac tumor cells reflecting extra-embryonal differentiation. OCT4 is lost upon differentiation. We used GCT derived cell lines of varying differentiation stages to analyze expression of HERVK and PRODH. Differentiation status and cellular relationship of GCT cells was determined using microarray analysis and western blotting of the embryonic pluripotency markers OCT4 and LIN28A. The highest expression of HERVK was found in undifferentiated EC cells, which retain a stem cell phenotype and express both OCT4 and LIN28. In contrast, the lowest expression of HERVK was observed in somatic differentiated GCT cells which also lack OCT4 and LIN28A whereas GCT cells with differentiation characteristics of yolk-sac tumor expressed LIN28A but not OCT4 and showed intermediate level of HERVK. A similar pattern was found for PRODH. Differentiation of EC cells by siRNA mediated knock-down of OCT4 or treatment with differentiation inducing medium decreased expression of HERVK and PRODH. Treatment of differentiated GCT cells with 5’-azacytidine and trichostatin A increased expression of HERVK and PRODH, indicating that epigenetic mechanisms are responsible for altered expression of these genes. Our data suggest that HERVK expression is dependent on cellular differentiation stages regulated by epigenetic mechanisms, which can also affect expression of neighboring genes.